ANALYSIS OF FACTORS ON SHARIA COMPLIANCE BASED ON AAOIFI STANDARDS - Indahyani, Sri Duyung; Riziqiyah, Metiya Fatikhatur; Krisnawati, Lina (Branding: Jurnal Manajemen dan Bisnis, 2025)
In order to determine what elements affect sharia compliance in Islamic banking in Indonesia, this research looked at the following: ownership, management traits, sharia board of directors’ expertise, and external audits based on AAOIFI criteria. Indonesian Sharia Business Units and Islamic Commercial Banks are the focus of this research. This study’s findings indicate that sharia compliance is unaffected by the factors of ownership and the level of expertise on the board of directors. According to the AAOIFI, sharia compliance is significantly affected by management traits and external audit factors.